Understanding discharge planning for post-cardiac catheterization and post-stroke clients - Fitriani, Dewi; Handoyo, Lukman; Yudiatma, M. Firman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Clients who have undergone cardiac catheterization and stroke treatment often require comprehensive preparation before being discharged from the hospital. Discharge planning plays a crucial role in ensuring continuity of care, improving patient understanding, and preventing recurrence or complications. In urban hospital settings, the complexity of care pathways, time limitations, and the absence of standardized procedures may affect the effectiveness of discharge planning for these high-risk clients. Purpose: To explore nurses’ experiences in implementing discharge planning for post-cardiac catheterization and post-stroke clients in urban hospitals. Method: A qualitative design using a descriptive phenomenological approach. Participants were nurses involved in the care of post-cardiac catheterization and post-stroke clients. Data were collected through in-depth interviews and analyzed thematically to capture the meaning of nurses’ lived experiences in discharge planning implementation. Results: Several key issues influencing discharge planning were identified. Patient admission pathways shaped the structure of discharge planning, with elective cases allowing more systematic education than emergency cases. Time constraints, particularly in CITO cases, led to rushed education. Nurses emphasized the need for visual educational media to improve patient understanding, while patient and family non-compliance remained a major challenge. The absence of specific SOPs, unstructured multidisciplinary collaboration, and the lack of written education forms and systematic checklists were identified as critical gaps in supporting post-discharge care. Conclusion: Discharge planning for post-cardiac catheterization and post-stroke clients in urban hospitals has not yet been implemented in a comprehensive and standardized manner. Its practice remains largely dependent on individual initiative, with limitations in structured education, interprofessional coordination, and systematic doc Suggestion: Strengthening the role of nurses as discharge planning coordinators, supported by standardized guidelines, structured education, and improved multidisciplinary collaboration, is recommended to enhance the effectiveness of discharge planning in urban hospital settings.